A Non-invasive System for Predicting Hemoglobin (Hb) in Dengue Fever (DF) and Dengue Hemorrhagic Fever (DHiF) - A. R., Herlina; I., Fatimah; T., Mohd. Nasir (2005)
Single frequency bioelectrical impedance analysis (BIA) is an inexpensive, quick and painless means of estimating body composition. In this paper, BIA parameters employed for predicting hemoglobin (Hb) in dengue patients. The BIA technique passes low-amplitude electrical current, in the range of 500pA to 800[A, at a single frequency of 50 kHz. BIA data was sampled from 210 (comprises of 119 males and 91 females) serologically confirmed dengue fever (DF) and dengue hemorrhagic fever (DHF) patients, hospitalized at the Hospital Universiti Kebangsaan Malaysia (HUKM). After applying multiple regression analysis, was found out that reactance, sex, weight and vomiting were found to be significant independent determinants of predicting Hb.